The Sports Badge "Fit For Work and Defence" ("Sprawny do Pracy i Obrony" - SPO). The Characteristics and Principles of Earning It on the Example of Sports Associations in Rzeszów Voivodship in 1953 - Agnieszka Mirkiewicz (Jan Długosz University in Częstochowa, 2020)
In 1950, using the Soviet GTO badge as a model, the SPO (BSPO) sports badge was introduced in Poland. It was the basis of the contemporary physical culture system and a factor of promoting mass sport. The badge was divided into 4 degrees and the following age categories were established: the kid degree BSPO with the division into two categories: 1) girls and boys aged 11 to 12, and 2) aged 13 to 14, as well as the youth degree BSPO with one age category: 15-16. SPO included degrees 1 and 2 and two age categories: 1) 17-35, 2) 36 and above. The regulations of earning the badge were prepared, special committees were appointed, and the whole process was supervised by the Main Committee of Physical Culture (Główny Komitet Kultury Fizycznej - GKKF). Political authorities attached a lot of importance to possessing that badge, and mass earning of the SPO badge was a priority for the contemporary sports authorities. Schools, universities, the army, People's Sports Teams and sports associations were obliged to conduct tests for the required standards for the SPO badge. This paper tries to answer the following questions: What criteria had to be met to be awarded the SPO and BSPO badge? and: How many badges were achieved in sports associations in Rzeszów Voivodship in 1953?